Cervical myelopathy due to neurovascular compression syndrome caused by persistent first intersegmental artery: a case report - Takuro Endo; Taku Sugawara; Naoki Higashiyama (BMC Neurology, 2020)
Abstract Background Persistent first intersegmental artery (PFIA) is a rare anatomical variation of vertebral arteries and is an asymptomatic finding in most cases. Here we report a rare case of cervical myelopathy caused by spinal cord compression by the PFIA. Case presentation The patient was a 52-year-old man who complained of numbness and burning sensation around the neck and left shoulder area, partial weakness in the left deltoid muscle, right side thermal hypoalgesia, and disturbance of deep sensation since the past 1 year, and the symptoms had gradually worsened. Magnetic resonance imaging (MRI) and computed tomography (CT) showed spinal cord compression by the left PFIA at the C1/C2 level. Because conservative treatment was ineffective, microvascular decompression (MVD) of the PFIA was performed. The left PFIA was laterally transposed using polytetrafluoroethylene (PTFE) bands and anchored to the dura mater using three PTFE bands. To achieve adequate transposition, the small blood vessels bridging the spinal cord and PFIA and the dorsal root nerve had to be sacrificed. Postoperative T2-weighted MRI showed a small hyperintense region in the lateral funiculus of the spinal cord, but no new neurological deficits were identified. In the early postoperative stage, the patient’s deep sensory impairment and motor dysfunction were improved. His numbness and burning sensation almost disappeared, but slight thermal hypoalgesia remained in the lower limb. Conclusion MVD is an effective treatment for spinal cord compression caused by the PFIA, but further studies are necessary to help address technical difficulties and avoid complications.